Shifting legal visions : judicial change and human rights trials in Latin America / Ezequiel A. González-Ocantos. - Gonzáles-Ocantos, Ezequiel A. (Cambridge studies in law and society., 2016)
What explains the success of criminal prosecutions against former Latin American officials accused of human rights violations? Why did some judiciaries evolve from unresponsive bureaucracies into protectors of victim rights? Using a theory of judicial action inspired by sociological institutionalism, this book argues that this was the result of deep transformations in the legal preferences of judges and prosecutors. Judicial actors discarded long-standing positivist legal criteria, historically protective of conservative interests, and embraced doctrines grounded in international human rights law, which made possible innovative readings of constitutions and criminal codes. Litigants were responsible for this shift in legal visions by activating informal mechanisms of ideational change and providing the skills necessary to deal with complex and unusual cases. Through an in-depth exploration of the interactions between judges, prosecutors and human rights lawyers in three countries, the book asks how changing ideas about the law and standards of adjudication condition the exercise of judicial power.